Stress exposure affects amyotrophic lateral sclerosis pathogenesis via PI3K/Akt and focal adhesion pathways: evidence from three experimental models - Daniela Maria Rasà; Ilaria Stoppa; Noémie Bérenger-Currias; Elena Pasho; Sorana Ciura; Edor Kabashi; Cécile Martinat; Marina Boido (Scientific Reports)
Abstract Amyotrophic lateral sclerosis (ALS) is a multifactorial motor neuron (MN) disease, characterized by several cellular dysfunctions, many of which are shared by different neurodegenerative diseases. Here, we investigated whether a stressful lifestyle might exacerbate the altered mechanisms and affect the disease progression in ALS-predisposed conditions. To model stress in vivo, SOD1 G93A mice underwent a chronic unpredicted mild stress protocol. This resulted in a significant impairment in body weight gain and motor performance, in a gender-specific manner. Moreover, the gene expression of Col1a1, Col1a2 and Il6 was strongly dysregulated in motor cortex and/or spinal cord of stressed mice. To assess the direct impact of stress on MNs, NSC-34 hSOD1 G93A cells underwent oxygen and glucose deprivation. Compared to NSC-34 hSOD1 WT, mutated MNs exhibited a reduced capacity to cope with stress. By performing gene expression, protein-protein interaction, gene ontology and pathway enrichment analyses, we also revealed the pivotal role of the PI3K/Akt and focal adhesion pathways (triggered by Gsk3b, Il6, Igf1 and/or collagen) in mediating stress response. Similar results were observed in stressed human iPSCs-derived TARDBP G298S MNs. In conclusion, our results suggest that the PI3K/Akt and focal adhesion pathways play a crucial role in stress response across different ALS-predisposed models: the study paves the way for novel therapeutic targets and highlights the relevance of a healthy lifestyle.